Republic of Poland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2012)
This Selected Issues Paper focuses on the economic and financial ties between Poland and the euro area and analyzes the associated spillovers. It documents stylized facts about trade, vertical integration, foreign direct investment, and banking system linkages between Poland and core euro area countries. The impact of shocks originating from the euro area on economic developments in Poland is quantified using two methods, namely a vector auto-regression model and a small-open-economy quarterly projection model.